Engineered silica nanoparticles act as adjuvants to enhance allergic airway disease in mice - Brandenberger, Christina (BioMed Central, 2013)
BACKGROUND: With the increase in production and use of engineered nanoparticles (NP; ≤ 100 nm), safety concerns have risen about the potential health effects of occupational or environmental NP exposure. Results of animal toxicology studies suggest that inhalation of NP may cause pulmonary injury with subsequent acute or chronic inflammation. People with chronic respiratory diseases like asthma or allergic rhinitis may be even more susceptible to toxic effects of inhaled NP. Few studies, however, have investigated adverse effects of inhaled NP that may enhance the development of allergic airway disease. METHODS: We investigated the potential of polyethylene glycol coated amorphous silica NP (SNP; 90 nm diameter) to promote allergic airway disease when co-exposed during sensitization with an allergen. BALB/c mice were sensitized by intranasal instillation with 0.02% ovalbumin (OVA; allergen) or saline (control), and co-exposed to 0, 10, 100, or 400 μg of SNP. OVA-sensitized mice were then challenged intranasally with 0.5% OVA 14 and 15 days after sensitization, and all animals were sacrificed a day after the last OVA challenge. Blood and bronchoalveolar lavage fluid (BALF) were collected, and pulmonary tissue was processed for histopathology and biochemical and molecular analyses. RESULTS: Co-exposure to SNP during OVA sensitization caused a dose-dependent enhancement of allergic airway disease upon challenge with OVA alone. This adjuvant-like effect was manifested by significantly greater OVA-specific serum IgE, airway eosinophil infiltration, mucous cell metaplasia, and Th2 and Th17 cytokine gene and protein expression, as compared to mice that were sensitized to OVA without SNP. In saline controls, SNP exposure did cause a moderate increase in airway neutrophils at the highest doses. CONCLUSIONS: These results suggest that airway exposure to engineered SNP could enhance allergen sensitization and foster greater manifestation of allergic airway disease upon secondary allergen exposures. Whereas SNP caused innate immune responses at high doses in non-allergic mice, the adjuvant effects of SNP were found at lower doses in allergic mice and were Th2/Th17 related. In conclusion, these findings in mice suggest that individuals exposed to SNP might be more prone to manifest allergic airway disease, due to adjuvant-like properties of SNP.